2014
DOI: 10.3171/2013.9.jns13921
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and clinical risk factors for posterior communicating artery aneurysm rupture

Abstract: Object Recent studies have shown that posterior circulation aneurysms, specifically posterior communicating artery (PCoA) aneurysms, are more likely to rupture than other aneurysms. To date, few studies have investigated the factors contributing to PCoA aneurysm rupture. The authors aimed to identify morphological and clinical characteristics predisposing to PCoA aneurysm rupture. Methods The authors retrospectively reviewed 134 consecutive patients with PCoA aneurysms managed at their facility between July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 43 publications
4
47
0
1
Order By: Relevance
“…The most important configurations in modern practice relate to the lateral versus inferior projection of the aneurysm dome since inferiorly projecting aneurysms commonly compress the oculomotor nerve while laterally projecting aneurysms can be tightly adherent to the temporal lobe and are sources of temporal lobe hemorrhage when ruptured. Recent investigation has also shown that ruptured aneurysms are associated with lateral projection of the aneurysm dome [37]. This relationship held true within our sample, where ruptured aneurysms (55%) were more associated with lateral projection than unruptured aneurysms (30%).…”
Section: Discussionsupporting
confidence: 86%
“…The most important configurations in modern practice relate to the lateral versus inferior projection of the aneurysm dome since inferiorly projecting aneurysms commonly compress the oculomotor nerve while laterally projecting aneurysms can be tightly adherent to the temporal lobe and are sources of temporal lobe hemorrhage when ruptured. Recent investigation has also shown that ruptured aneurysms are associated with lateral projection of the aneurysm dome [37]. This relationship held true within our sample, where ruptured aneurysms (55%) were more associated with lateral projection than unruptured aneurysms (30%).…”
Section: Discussionsupporting
confidence: 86%
“…The strongest independent risk factors include smoking, asymmetry of A1 segments >40%, low blood flow pulsatility, and angle between A1 and A2 segments ≤100°. Matsukawa et al 16 retrospectively reviewed 134 consecutive patients with PcomA aneurysms (39 ruptured) and compared the morphological and clinical characteristics. The results showed that age <60 years, history of hypertension, lateral direction of the aneurysmal dome, and bleb formation were significantly associated with aneurysm rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The arteriosclerosis and calcification of the parent artery in type II and III cases easily led to intraoperative rupture during aneurysm clipping, with type III aneurysms having a greater risk of intraoperative rupture than type II because the aneurysm neck and parent artery exhibited arteriosclerosis or calcification. There are many techniques for clipping PCoA aneurysms, with >100 types of intracranial aneurysm clips available (25). Among them, fenestrated clips for PCoA aneurysm clipping are occasionally used (26).…”
Section: Discussionmentioning
confidence: 99%